Analisis Pengaruh Umur & Gender Terhadap Perilaku Beresiko Pengendara Sepeda Motor Yang Dapat Menimbulkan Kecelakan Lalu Lintas Di Kota Denpasar - Oktaviani Putri, Asta; Dewi, I Gusti Ayu Wulan Krisna; Rani, Ni Made Sintya (Universitas Pendidikan Nasional, 2025)
This study examines the effect of age and gender on motorbike risk behavior in the city of Denpasar, Bali Province, Indonesia. Questionnaires were distributed to collect various data consisting of personal characteristics involving age and sex consisting of perceptions of risk (Risk Perception/RP), penchant for risk behavior (Positive Affect/PA), and risk driving behavior (Risk Behaviour/RB). The results showed that there were no significant differences between the age and gender of motorcyclists in performing risky behavior on the highway. Both teenagers and adults, as well as male or female drivers have the same possibility of behaving at risk on the road. Perceptions of risk behavior are very influential for motorbike riders, men, women, and adolescents. While perceptions and hobbyist behavior risk having an effect on adult motorcyclists. This shows that returning decisions when riding motorbikes on the road for male, female, and teenage motorbike riders is often based on rational analysis (perception) compared to the empirical experience of the rider based on driving experience. Unlike the adult motorcycle rider who takes into account the rational aspects and aspects of experience. Perception of risk behavior (RP) depends on the level of understanding or knowledge related to the definition of risk behavior on the highway. Therefore, education on road safety should start from an early age and become part of formal education in schools